Canine polarized macrophages express distinct functional and transcriptomic profiles - Chow, Lyndah; Soontararak, Sirikul; Wheat, William; Ammons, Dylan; Dow, Steven (Frontiers in Veterinary Science, 2022)
Macrophage differentiation and function in disease states is highly regulated by the local microenvironment. For example, macrophage exposure to IFN-γ (interferon gamma) initiates the development of inflammatory (M1) macrophages, which acquire anti-tumoral and antimicrobial activity, while exposure to IL-4 (interleukin-4) and IL-13 (interleukin-13) drives an anti-inflammatory (M2) macrophage phenotype, which promotes healing and suppression of inflammatory responses. Previous studies of canine polarized macrophages have identified several surface markers that distinguished GM-CSF (granulocyte macrophage colony stimulating factor), IFN-γ and LPS (lipopolysaccharide) derived M1 macrophages or M2 macrophages; and reported a subset of genes that can be used to differentiate between polarization states. However, the need remains to understand the underlying biological mechanisms governing canine macrophage polarization states. Therefore, in the present study we used transcriptome sequencing, a larger panel of flow cytometry markers, and the addition of antimicrobial functional assays to further characterize canine macrophage polarization. Transcriptome analysis revealed unique, previously unreported signatures and pathways for polarized canine M1 and M2 macrophages. New flow cytometric markers were also identified, along with new characterization of how macrophage polarization impacted antimicrobial functions. Taken together, the findings reported here provide new insights into canine macrophage biology and identify new tools for the evaluation of polarized macrophages in dogs.